2016
DOI: 10.17159/2221-4070/2016/v5i2a3
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and Children's Real-Life Schooling Experiences in Swaziland

Abstract: This paper foregrounds vulnerable children as a social group whose experiences should be studied and understood from their own perspectives. The paper explores the real-life schooling experiences of six Grade 6 vulnerable children, aged between 11-15 years, in a rural primary school in the Lubombo region of Swaziland. Guided by a theoretical paradigm of social constructionism, the paper engages dynamics of children's vulnerability within this context, ravaged by poverty and HIV and AIDS. The aim is to contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Swaziland's education policy defines vulnerable children as children who are orphaned, living in childheaded households, and children from resource-poor social and economic backgrounds (Swaziland Ministry of Education and Training, 2011). These children are locally referred to as bantfwana bendlunkhulu [those cared for by the whole community]; their educational fees are catered for by the government (Motsa & Morojele, 2016). HIV and AIDS, the main precipitators of parental deaths in Swaziland, expose many schoolgirls to the above-stated vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Swaziland's education policy defines vulnerable children as children who are orphaned, living in childheaded households, and children from resource-poor social and economic backgrounds (Swaziland Ministry of Education and Training, 2011). These children are locally referred to as bantfwana bendlunkhulu [those cared for by the whole community]; their educational fees are catered for by the government (Motsa & Morojele, 2016). HIV and AIDS, the main precipitators of parental deaths in Swaziland, expose many schoolgirls to the above-stated vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the current study therefore provide further justification for the positive experiences that emaSwati youth can be exposed to if concerted efforts are made to invest in sport-based positive developmental experiences. In addition, the coaching bonds developed through this program were described by the youth and coaches as positive but also vastly different from the normal adult-child relationships experienced by youth (and especially socially vulnerable youth) in eSwatini that are typified as autocratic with unequal power dynamics (Motsa & Morojele, 2016). This type of sport programming therefore exposed youth to opportunities for positive attachment and connection to adult figures that are not normally available to them in their larger everyday lived experience.…”
Section: Research Question One: Youth Participation Experiencesmentioning
confidence: 99%
“…Principles of reinforcement have a long history in the education system to influence student behavior and the combined use of punishment and reward has been identified as an effective behavioral management strategy (Hamilton, 2016). In the school system in eSwatini, the use of punishment and reward is a widespread practice so it is a behavior management strategy that youth experience frequently (Motsa & Morojele, 2016). Notably, one study conducted in eSwatini reported that the use of corporal punishment is often higher for vulnerable children given that they often fail to comply with strict school rules related to homework completion and dress code because of their social circumstances of neglect (Motsa & Morojele, 2016).…”
Section: Coaching Strategiesmentioning
confidence: 99%
See 2 more Smart Citations